Numerical approximation of the fractional Laplacian on R using orthogonal families - Cayama, Jorge; Cuesta, Carlota M.; de la Hoz, Francisco (Applied numerical mathematics, 2020)
In this paper, using well-known complex variable techniques, we compute explicitly, in terms of the F12 Gaussian hypergeometric function, the one-dimensional fractional Laplacian of the complex Higgins functions, the complex Christov functions, and their sine-like and cosine-like versions. Then, after studying the asymptotic behavior of the resulting expressions, we discuss the numerical difficulties in their implementation, and develop a method using arbitrary-precision arithmetic that computes them accurately. We also explain how to create the differentiation matrices associated to the complex Higgins functions and to the complex Christov functions, and study their condition numbers. In this regard, we show how arbitrary-precision arithmetic is the natural tool to deal with ill-conditioned systems. Finally, we simulate numerically the fractional nonlinear Schrödinger equation using the developed tools.